Perception of Students and Teachers Regarding Online Teaching-learning during Pandemic Time - Vakil, Manisha R; Kakde, Haresh (JOURNAL OF INDIAN EDUCATION, 2023)
Internet and new technologies gained importance in several fields including education sector, which gave the scope for online classes. In addition to this, the COVID-19 pandemic worldwide has also added to the need and relevance of online classes making it necessary to understand student–teacher perceptions regarding online classes. The study is aimed at analysing the perception of teachers and students about online classes. It tries to explain the opinions of students with regards to the impact of online courses, their comfortability in its usage, and the support received from teachers in online classes along with teachers’ opinions on efficacy, teaching practice followed and training received for an online class. The analysis was carried out using the data collected through two separate structured questionnaires for students and teachers in Vadodara district of Gujarat. Data were recorded in SPSS and analysed using descriptive statistics. The study reveals that students are comfortable with online classes and are getting enough support from teachers but they do not believe that online classes will replace traditional classroom teaching. It also finds that teachers are facing difficulties in conducting online classes due to a lack of proper training and development for doing online classes. Technical issues are the major problem for the effectiveness of the online classes. This study helps schools get a general view of online classes among teachers and students.